Transtorno do desenvolvimento da coordenação em escolares prematuros : estudo bibliométrico e de prevalência - Coppede, Aline Cirelli (2015)
Studies show that among the several changes that premature infants may present, the Developmental Coordination Disorder (DCD) has highlighted. The incidence in this population is between 30 to 50%. Thus, there is necessary research in this field of knowledge in order to identify existing subject of this in the sciencitifc literature, the gaps to be filled and the prospects and trends in this area. The aim of this study was to verify how is the field of literature in national and international databases on Developmental Coordination Disorder among premature infants, and estimate the prevalence of Development Coordination Disorder (DCD) in elementary school children in Ribeirão Preto. The research is descriptive, exploratory and analytical. Quantitative methods were adopted and the research was divided into two studies. Study 1 refers to bibliometric analysis of scientific literature on TDC in premature available in national and international databases. The recovered articles have undergone a thorough review, and were produced bibliometric indicators on the profile of studies: year of publication, language, authorship, journal, participants, instruments used, design. Study 2 is to identify the prevalence of DCD in students from public and private schools in a city located in State of São Paulo. Participated in the survey, 315 school-age children with (6-13 years) and their parents. The instruments used were the Economic Classification Criteria Brazil, the questionnaire DCDQ - Developmental Coordination Disorder Questionnaire - Brazilian version, the Swanson, Nolan and Pelham Scale IV - SNAP IV and the Movement Assessment Battery Scale for Children-2 (MABC-2). Data were analyzed from spreadsheets of each instrument and descriptive statistical studies, were made comparative and correlational. The results showed that the publications on DCD in premature infants has increased in recent years, the predominant language is English, the authorship is collective, and Lotka's Law is confirmed; the country that stands out most is Australia (30%), most studies are descriptive cross-sectional (61%) and use the MABC-2 as test (50%). In study 2, 33% of children had risk TDC with a significant difference between the groups; The proportion of children with risk for TDC is 75% higher among premature infants in GII and 83% in GIII. The prevalence of children at risk for TDC is higher in public schools (45%) than in the private school (20%) in GIII; 17% of the children had scores to TDC, 7% moderate and 10% severe; 12% showed signs of ADHD. The DCDQ was onsidered valid by the M-ABC-2; and tests showed high association between them. It is observed that the effect of age presents significance, in which the group III prevalence is 1.75 times greater than the group I. The groups I and II do not differ. The effect of prematurity has significance, in which preterm infants have a prevalence of DCD 2.47 times greater than those born at term. The studies complement each presenting an overview of the state of the art production of scientific knowledge on TDC in premature showing gaps and trends in this area, guiding future studies. The prevalence study identifies correctly the children with signs and symptoms of TDC, is essential so that difficulties are assessed and an individual action plan is formulated, preventing future complications.